Patient and provider perspectives on the design and implementation of an electronic consultation system for kidney care delivery in Canada: a focus group study. Issue 3 (2nd March 2017) - Bello, Aminu K; Molzahn, Anita E; Girard, Louis P; Osman, Mohamed A; Okpechi, Ikechi G; Glassford, Jodi; Thompson, Stephanie; Keely, Erin; Liddy, Clare; Manns, Braden; Jinda, Kailash; Klarenbach, Scott; et al.
Abstract : Objectives: We assessed stakeholder perceptions on the use of an electronic consultation system (e-Consult) to improve the delivery of kidney care in Alberta. We aim to identify acceptability, barriers and facilitators to the use of an e-Consult system for ambulatory kidney care delivery. Methods: This was a qualitative focus group study using a thematic analysis design. Eight focus groups were held in four locations in the province of Alberta, Canada. In total, there were 72 participants in two broad stakeholder categories: patients (including patients' relatives) and providers (including primary care physicians, nephrologists, other care providers and policymakers). Findings: The e-Consult system was generally acceptable across all stakeholder groups. The key barriers identified were length of time required for referring physicians to complete the e-Consult due to lack of integration with current electronic medical records, and concerns that increased numbers of requests might overwhelm nephrologists and lead to a delayed response or an unsustainable system. The key facilitators identified were potential improvement of care coordination, dissemination of best practice through an educational platform, comprehensive data to make decisions without the need for face-to-face consultation, timely feedback to primary care providers, timeliness/reduced delays for patients' rapid triage and identification of cases needing urgent care and improved access to information to facilitate decision-making in patient care. Conclusions: Stakeholder perceptions regarding the e-Consult system were favourable, and the key barriers and facilitators identified will be considered in design and implementation of an acceptable and sustainable electronic consultation system for kidney care delivery.